1988
DOI: 10.1016/s0195-5616(88)50051-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid

Abstract: It is hoped that we have demonstrated that collection, handling, and limited analysis of CSF samples from the dog and cat are relatively simple. No special equipment or handling is required, and the procedures are within the capabilities of any veterinarian interested in performing them. In addition, although this article was not intended to present a detailed discussion on the interpretation of the analysis of CSF, we have demonstrated some very practical interpretations to the various aspects of a routine CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 8 publications
0
50
1
Order By: Relevance
“…A small aliquot of the obtained sample must be saved separately in sterile plastic vials for microbiological testing (culture and sensitivity) if an infectious disorder is suspected. It has been anecdotally stated that cytological evaluation of CSF samples should be done within 30 minutes from collection, as subsequent cell degeneration associated with its low protein content (Cook and DeNicola, 1988;Oliver and Lorenz, 1993). More recent studies on the effects of time, composition and addition of stabilizing agents have concluded that CSF samples have to be processed as soon as possible, however delayed (from 4 up to 8 hours) analysis may not alter clinical interpretation significantly (Fry et al, 2006).…”
Section: Csf Sample Handlingmentioning
confidence: 99%
See 4 more Smart Citations
“…A small aliquot of the obtained sample must be saved separately in sterile plastic vials for microbiological testing (culture and sensitivity) if an infectious disorder is suspected. It has been anecdotally stated that cytological evaluation of CSF samples should be done within 30 minutes from collection, as subsequent cell degeneration associated with its low protein content (Cook and DeNicola, 1988;Oliver and Lorenz, 1993). More recent studies on the effects of time, composition and addition of stabilizing agents have concluded that CSF samples have to be processed as soon as possible, however delayed (from 4 up to 8 hours) analysis may not alter clinical interpretation significantly (Fry et al, 2006).…”
Section: Csf Sample Handlingmentioning
confidence: 99%
“…The latter is an uncommon cause of CSF red coloration because free erythrocytes start to degenerate within 1-4 hours in the subarachnoid space and fluid collection rarely coincides with their presence. In this case, sample centrifugation results in the formation of a erythrocyte "pellet" at the bottom of the tube while the supernatant remains clear (Cook and DeNicola, 1988). The presence of pink or reddish, "thread-like" swirls during CSF flow into the sampling vial suggest iatrogenic blood contamination (Levine and Levine, 2012).…”
Section: Csf Sample Analysis Gross Appearancementioning
confidence: 99%
See 3 more Smart Citations